ANALYSIS OF GOVERMENT AND COMMUNITY PREPAREDNES IN TERBOYO INDUSTRIAL AREA, GENUK DISTRICT FACING FLOODS - Nurhaliza, Ira; Mulianingsih, Ferani (Penerbit Lafadz Jaya, 2026)
Terboyo Industrial Area, Genuk District, Semarang City faces recurrent flooding due to extreme rainfall, land subsidence, and poor drainage, disrupting industrial operations and community livelihoods. This study analyzes government and community preparedness levels, examining synergy between Disaster Preparedness Forums and infrastructure responses. Employing a qualitative descriptive approach, purposive sampling targeted 12 key informants from BPBD, subdistrict officials, and community leaders across 10 flood-prone villages. Data collection utilized semi-structured interviews, participant observation, and BPBD document analysis, with Miles and Huberman's model for thematic coding, data display, and triangulation ensuring credibility. Findings reveal government initiatives including portable pumps, color-coded flood mapping, and emergency facilities, alongside community efforts in evacuation planning and environmental maintenance. However, disaster literacy gaps and coordination weaknesses persist. Conclusions emphasize government-community synergy through enhanced education, real-time early warning systems, and FSB capacity building for sustainable resilience.